Fish Health Management Through Utilization of Natural Materials - Mulia, Dini Siswani; Purbomartono, Cahyono; Wuliandari, Juli Rochmijati (Altifani Journal: International Journal of Community Engagement, 2022)
Freshwater fish farming is appealing to parents and adolescents, including Madrasah Aliyah Miftahussalam, Banyumas students. However, partners frequently find diseased fish. This exercise seeks to improve partners' awareness of fish health management using natural substances. The method of activities carried out includes coordinating the preparation of activities with partners, compiling modules, implementing activities, and evaluating the results of actions. The implementation of the activities was carried out in 4 stages, namely pre-test, delivery of material, discussion and question-answer, and post-test. The pre-post test data were analyzed using a paired T-test. The activity was declared victorious with an indicator of increasing knowledge and understanding of at least 30%. The data analysis results showed a difference in the average value of the pre-post test with a significance value of 0.000 <0.05. These results indicate that service activities have a positive effect on increasing partner knowledge and understanding. The average value obtained at the pre-test was 50, then increased at the post-test to 74.35. The post-test results increased by 48.7% compared to the pre-test. This result is higher than the planned achievement target of 30%. Based on the reality and the questionnaire results, the partners were very enthusiastic about participating in this service activity. Service activities will continue to be carried out as a form of concern and transfer of science and technology to the community, as well as the application of the tri dharma of higher education.